(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The Indian Independence League and the Indian National Army (INA) nationalist myth (IIL).Few historians explore the motivations behind the British Indian Army troops’ decision to join the INA aswell as how confinement and the strains of war affected their choices. It is a whitewash of history and adisregard for the complexities of a complicated historical issue to dismiss the many reasons why peoplejoined the INA and the IIL. Despite the Sikh community’s extensive cooperation with the colonialauthorities, the Shiromani Akali Dal received nothing on the eve of the British departure in 1947 whereasthe All-India Muslim League and the Indian National Congress both obtained Pakistan and India. As aresult of the division of the Indian subcontinent, the Sikh community’s demands for a distinct Sikh stateand the addition of further regions to this state were unsuccessful. The Akali leadership’s choice to joinIndia enslaved their group to a massive majority in which they made up barely 1.